(untitled) (Research, Society and Development, 2023)
This study aimed to conduct an integrative literature review to explore the role of primary health care nurses in the care and guidance of sexuality during the climacteric period. The methodology used consisted of a search and analysis of scientific studies in electronic databases, scientific journals and theses/dissertations relevant to the topic. Studies were included that addressed the role of nurses in the orientation and care of sexuality during the climacteric period, as well as the results obtained. The results of the review showed that nurses play an important role in this phase of women’s lives. The role ranges from providing clear and updated information about the physical and psychological changes of the climacteric period, to emotional support and guidance on healthy and safe sexual practices. It was verified that nurses have the ability to establish a relationship of trust and empathy with women in the climacteric stage, which enables the opening of discussions about intimate and sensitive issues related to sexuality. In conclusion, this study highlights the importance of Primary Health Care nurses in the care and guidance of sexuality during the climacteric period. Nurses should be prepared to address such issues in a sensitive and welcoming way, providing adequate information and promoting sexual health and self-care for women in the climacteric period. This comprehensive approach contributes to a better quality of life and well-being of women in this phase of life.